KELAYAKAN PENUNTUN PRAKTIKUM UNTUK PRAKTIKUM PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Nursapikka, Endi; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to determine the feasibility of laboratory work guidance for making pineapple (Ananas comosus (L.) Merr.) candy on the subchapter of the role of plants in economic class X high school. The research was conducted by using descriptive method Â with validation conducted by 2 lecturers from biology education and 3 biology teachers from senior high school. The validation devided into two steps, the first step was validation intrument of laboratory work guidance and the second step was validation media laboratory work guidance. Based on validation result of laboratory work guidance, there was 15 criteria with CVR value equal to 0.99 in accordance with minimum CVR value of Lawshe for 5 validator was 0.99, so the laboratory work guidance was feasible and can be implemented as a learning media to guide the laboratory work of making pineapple (Ananas comosus (L.) Merr) candy on subchapter Role of Plant In Economic Class X High School.Â Keywords: Feasibility, Practicum Guidance, Pineapple Candy